Evolutionary History, Immigration History, and the Extent of Diversification in Community Assembly - Knope, Matthew L.; Forde, Samantha E.; Fukami, Tadashi (Frontiers in Microbiology, 2012)
During community assembly, species accumulate by both immigration and in situ diversification. Diversification has intrigued biologists because its extent varies even among closely related lineages under similar ecological conditions. Recent research has suggested that some of this puzzling variation may be caused by stochastic differences in the history of immigration (relative timing and order of immigration by founding populations), indicating that immigration and diversification may affect community assembly interactively. However, it remains unclear under what conditions immigration history affects diversification. Here we propose the hypothesis that whether or not immigration history influences the extent of diversification depends on the founding populations’ prior evolutionary history, using evidence from a bacterial experiment. To create genotypes with different evolutionary histories, replicate populations of Pseudomonas fluorescens were allowed to adapt to a novel environment for a short or long period of time (approximately 10 or 100 bacterial generations) with or without exploiters (viral parasites). Each evolved genotype was then introduced to a new habitat either before or after a standard competitor genotype. Most genotypes diversified to a greater extent when introduced before, rather than after, the competitor. However, introduction order did not affect the extent of diversification when the evolved genotype had previously adapted to the environment for a long period of time without exploiters. Diversification of these populations was low regardless of introduction order. These results suggest that the importance of immigration history in diversification can be predicted by the immigrants’ evolutionary past. The hypothesis proposed here may be generally applicable in both micro- and macro-organisms.